Locally acquired lymphocytic choriomeningitis virus infections in South‐East Queensland: an outbreak of a pathogen rarely described in Australia. Issue 8 (16th August 2022) - Aaron, Luke; McMahon, Jamie; Taylor, Carmel; Pyke, Alyssa T.; Brischetto, Anna; Aminzadeh, Zohreh; Beale, Mark
Abstract: Lymphocytic choriomeningitis virus (LCMV) is a zoonotic virus that can cause clinically significant illnesses in humans. Although cases of LCMV infection are well described globally, and there is evidence that the virus is present in Australian rodent populations, there has been only one case of domestically acquired LCMV infection published previously. Here, we describe a cluster of LCMV infections in South‐East Queensland identified in early 2021, and the diagnostic testing processes implemented. This identifies LCMV as an under‐recognised human pathogen in Australia.